Application of a Dual Internally Quenched Fluorogenic Substrate in Screening for D-Arginine Specific Proteases - Simon, Andreas H.; Liebscher, Sandra; Aumüller, Tobias H.; Treblow, Dennis; Bordusa, Frank (Frontiers in Microbiology, 2019)
The application of D-stereospecific proteases (DSPs) in resolution of racemic amino acids and in the semisynthesis of proteins has been a successful strategy. The main limitation for a broader application is however the accessibility of suitable DSPs covering multiple substrate specificities. To identify DSPs with novel primary substrate preferences, a fast specificity screening method using the easily accessible internally quenched fluorogenic substrate aminobenzoyl-D-arginyl-D-alanyl-p-nitroanilide was developed. By monitoring both UV/vis-absorbance and fluorescence signals at the same time it allows to detect two distinct D-amino acid substrate specificities simultaneously and separately with respect to the individual specificities. In order to identify novel DSP specificities for synthesis applications, DSPs specific for D-arginine were of special interest due to their potential ability as catalysts for substrate mimetics-mediated peptide and protein ligations. D-alanine in the substrate served as positive control and reference based on its known acceptance by numerous DSPs. In silico analysis suggested that DSPs are predominantly present in gram-positive microorganisms, therefore this study focused on the bacilli strains B. thuringiensis and B. subtilis as potential hosts of D-Arg-specific DSPs. While protease activities towards D-alanine were found in both organisms, a novel and so far unknown D-arginine specific DSP was detected within the culture supernatant of B. thuringiensis. Enrichment of this activity via cation exchange and size exclusion chromatography allowed isolation and further characterization of this novel enzyme consisting of a molecular mass of 37.7 kDa and an enzymatic activity of 8.3 U mg-1 for cleaving the D-Arg|D-Ala bond in the detecting substrate. Independent experiments also showed that the identified enzyme shows similarities to the class of penicillin binding proteins. In future applications this enzyme will be a promising starting point for the development of novel strategies for the semisynthesis of all-L-proteins.